Book Review - Darnaedi, Dedy (REINWARDTIA, 2012)
B.S. Parris, R. Kiew, R.C.K. Chung, L.G. Saw & E. Soepadmo (eds). 2010. Flora of Peninsular Malaysia, Series I. Ferns and Lycophytes. VolÃÂ  1. Malayan Forest Records No. 48. Forest Research Institute Malaysia, Ministry of Natural Resources and Environment, Malaysia, 249 pp. Price: RM80/USD60.